(untitled) (Research, Society and Development, 2022)
Objective: To account the number of cases of Cervical Cancer in northeastern Brazil from the cytopathological examination (Pap smear). Methodology: This is a descriptive and retrospective cross-sectional study with a literary approach. The electronic search for information regarding the results of the cytopathological exams was taken from the Cancer Information System - SISCAN. Results: Data collection showed that between 2015 and 2019 a total of 16,952,217 cytological tests (pap smears) were performed throughout Brazil. In the Brazilian Northeast, it was possible to observe a coverage of 5,172,360 exams performed in the same period of time. These data are displayed in the graph below. Conclusion: the study revealed an expressive magnitude of new cases, and a relative number of deaths in relation to the researched age group. It was also observed that there was a significant increase in the number of preventive exams, which means an effective tracking activity carried out by primary care, given that it is responsible for performing most of these exams.